Superpixel Technique Enabled Spatial Phase Modulation Equalization for Power-Efficient Vortex Beam Generation - Ruhao Zhao; Junpeng Zheng; Cong Zhang; Meng Xiang; Gai Zhou; Yi Xu; Yuwen Qin; Songnian Fu (IEEE Photonics Journal)
Realizing a spatial phase modulation (SPM) from 0 to 2π is vital for achieving precise light field manipulation, when the phase-only spatial light modulator (SLM) is driven by the voltage. However, insufficient bias voltage degrades the quality of the generated structured light. Here, we propose a superpixel method that consists of 2 × 2 adjacent pixels to equalize the imperfect SPM response, when the bias voltage is insufficient. Meanwhile, a look-up table (LUT) is established between the target light field and the superpixel equalized light field, for reducing the computational complexity of phase hologram generation. When the phase modulation depth is reduced from 2π to 1.67π, we can generate the vortex beams with better quality by the superpixel technique. Characterizing the spatial phase distribution of vortex beams through interferometry verifies the correct function of the superpixel enabled SPM equalization method. In addition, the peak signal-to-noise ratio (PSNR) is used as the metric to quantitatively evaluate the quality of the generated vortex beam. Compared with the phase modulation distortion caused by the insufficient bias voltage, the PSNR after the superpixel enabled SPM equalization is improved by 4.5 dB. Our results would facilitate various applications mediated by power-efficient phase modulation utilizing the SLM.